A few Thomas’ Neologisms (from the Commentary on John) not registered in Lexicons. A contribution to the study of Thomas’ language and Medieval Latin Lexicography (Circe de clásicos y modernos, 2018)
Our objective is twofold: 1) to point out the convenience of incorporating some possible neologisms or other words found in Aquinas’ Commentary on John in future editions of lexicons or in new works devoted to Medieval Latin; 2) to reflect on the problems that a nonspecialist reader may face when consulting the common Latin dictionaries.
Keywords: Thomas Aquinas; lexicon; neologism; Commentary on John